2021
DOI: 10.1016/j.gendis.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A novel ABCD1 G1202A mutation in a Chinese patient with pure adrenomyeloneuropathy and literature review

Abstract: Adrenomyeloneuropathy (AMN) is a kind of varied disease caused by ABCD1 gene mutation and characterized by very-long-chain fatty acids (VLCFA) accumulation. It is diagnosed by clinical features, high VLCFAs levels and ABCD1 gene mutation. AMN is rarely reported in Chinese population. In this study, we report the genetic and clinical features of a Chinese pure AMN patient. Meanwhile, we conducted a literature review of AMN cases to summarize the characteristics of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A summary of all the AMN cases reported worldwide between 1975 and 2019 found that the mutations most frequently occurred in exon 1 of the ABCD1 gene, and most of them were missense mutations. [2] Genetic testing of our patient revealed a nucleotide mutation in exon 1 of the ABCD1 gene with a change from C to T in the coding region 761 (Fig. 3A), which resulted in a missense mutation in the amino acid 254 from threonine to methionine.…”
Section: Discussionmentioning
confidence: 98%
“…A summary of all the AMN cases reported worldwide between 1975 and 2019 found that the mutations most frequently occurred in exon 1 of the ABCD1 gene, and most of them were missense mutations. [2] Genetic testing of our patient revealed a nucleotide mutation in exon 1 of the ABCD1 gene with a change from C to T in the coding region 761 (Fig. 3A), which resulted in a missense mutation in the amino acid 254 from threonine to methionine.…”
Section: Discussionmentioning
confidence: 98%
“…(3) AMN is characterized by a chronic progressive axonopathy affecting sensory ascending and motor descending spinal cord tracts, leading to progressive spastic paraparesis, peripheral neuropathy, ataxia, sphincter incontinence, and sexual dysfunction, sometimes accompanied by adrenal insu ciency. (3)(4)(5)(6) There are currently no effective treatments for preventing, stabilizing, or reversing AMN progression.…”
Section: Introductionmentioning
confidence: 99%